What is the value of x, when

     

(x-1)(x+3)(x-2)(x-6)+36=0

This solution deals with finding the roots (zeroes) of polynomials.

Bạn đang xem: What is the value of x, when


Step by Step Solution

*

Step by step solution :

Step 1 :

Equation at the kết thúc of step 1 : (((x-1)•(x+3)•(x-2))•(x-6))+36 = 0

Step 2 :

Equation at the kết thúc of step 2 : ((x-1)•(x+3)•(x-2)•(x-6))+36 = 0

Step 3 :

Equation at the kết thúc of step 3 : (x-1)•(x+3)•(x-2)•(x-6)+36 = 0

Step 4 :

Step 5 :

Pulling out lượt thích terms :5.1 Pull out lượt thích factors:x4 - 6x3 - 7x2 + 48x=x•(x3 - 6x2 - 7x + 48)

Checking for a perfect cube :

5.2x3 - 6x2 - 7x + 48 is not a perfect cube

Trying to factor by pulling out :

5.3 Factoring: x3 - 6x2 - 7x + 48 Thoughtfully split the expression at hand into groups, each group having two terms:Group 1: -7x + 48Group 2: -6x2 + x3Pull out from each group separately :Group 1: (-7x + 48) • (1) = (7x - 48) • (-1)Group 2: (x - 6) • (x2)Bad news !! Factoring by pulling out fails : The groups have no common factor and can not be added up to size a multiplication.

Polynomial Roots Calculator :

5.4 Find roots (zeroes) of : F(x) = x3 - 6x2 - 7x + 48Polynomial Roots Calculator is a set of methods aimed at finding values ofxfor which F(x)=0 Rational Roots kiểm tra is one of the above mentioned tools. It would only find Rational Roots that is numbers x which can be expressed as the quotient of two integersThe Rational Root Theorem states that if a polynomial zeroes for a rational numberP/Q then p. Is a factor of the Trailing Constant và Q is a factor of the Leading CoefficientIn this case, the Leading Coefficient is 1 và the Trailing Constant is 48. The factor(s) are: of the Leading Coefficient : 1of the Trailing Constant : 1 ,2 ,3 ,4 ,6 ,8 ,12 ,16 ,24 ,48 Let us kiểm tra ....

Xem thêm: Các Bài Hát Của The Men Trình Bày, Những Bài Hát Do Ca Sĩ The Men Trình Bày

PQP/QF(P/Q)Divisor
-11 -1.00 48.00
-21 -2.00 30.00
-31 -3.00 -12.00
-41 -4.00 -84.00
-61 -6.00 -342.00
-81 -8.00 -792.00
-121-12.00-2460.00
-161-16.00-5472.00
-241-24.00-17064.00
-481-48.00-124032.00
11 1.00 36.00
21 2.00 18.00
31 3.00 0.00x - 3
41 4.00 -12.00
61 6.00 6.00
81 8.00 120.00
121 12.00 828.00
161 16.00 2496.00
241 24.0010248.00
481 48.0096480.00

The Factor Theorem states that if P/Q is root of a polynomial then this polynomial can be divided by q*x-p lưu ý that q and phường originate from P/Q reduced to its lowest terms In our case this means that x3 - 6x2 - 7x + 48can be divided with x - 3

Polynomial Long Division :

5.5 Polynomial Long Division Dividing : x3 - 6x2 - 7x + 48("Dividend") By:x - 3("Divisor")

dividendx3-6x2-7x+48
-divisor* x2x3-3x2
remainder-3x2-7x+48
-divisor* -3x1-3x2+9x
remainder-16x+48
-divisor* -16x0-16x+48
remainder0

Quotient : x2-3x-16 Remainder: 0

Trying lớn factor by splitting the middle term

5.6Factoring x2-3x-16 The first term is, x2 its coefficient is 1.The middle term is, -3x its coefficient is -3.The last term, "the constant", is -16Step-1 : Multiply the coefficient of the first term by the constant 1•-16=-16Step-2 : Find two factors of -16 whose sum equals the coefficient of the middle term, which is -3.

Xem thêm: Trường Học Của Những Chiến Binh Nụ Cười Candy And Smile Precure

-16+1=-15
-8+2=-6
-4+4=0
-2+8=6
-1+16=15

Observation : No two such factors can be found !! Conclusion : Trinomial can not be factored

Equation at the end of step 5 :

x • (x2 - 3x - 16) • (x - 3) = 0

Step 6 :

Theory - Roots of a product :6.1 A product of several terms equals zero.When a sản phẩm of two or more terms equals zero, then at least one of the terms must be zero.We shall now solve each term = 0 separatelyIn other words, we are going to solve as many equations as there are terms in the productAny solution of term = 0 solves hàng hóa = 0 as well.

Solving a Single Variable Equation:6.2Solve:x = 0 Solution is x = 0

Parabola, Finding the Vertex:6.3Find the Vertex ofy = x2-3x-16Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up & accordingly has a lowest point (AKA absolute minimum).We know this even before plotting "y" because the coefficient of the first term,1, is positive (greater than zero).Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want lớn be able lớn find the coordinates of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is given by -B/(2A). In our case the x coordinate is 1.5000Plugging into the parabola formula 1.5000 for x we can calculate the y-coordinate:y = 1.0 * 1.50 * 1.50 - 3.0 * 1.50 - 16.0 or y = -18.250

Parabola, Graphing Vertex and X-Intercepts :

Root plot for : y = x2-3x-16 Axis of Symmetry (dashed) x= 1.50 Vertex at x,y = 1.50,-18.25 x-Intercepts (Roots) : Root 1 at x,y = -2.77, 0.00 Root 2 at x,y = 5.77, 0.00

Solve Quadratic Equation by Completing The Square

6.4Solvingx2-3x-16 = 0 by Completing The Square.Add 16 khổng lồ both side of the equation : x2-3x = 16Now the clever bit: Take the coefficient of x, which is 3, divide by two, giving 3/2, và finally square it giving 9/4Add 9/4 to lớn both sides of the equation :On the right hand side we have:16+9/4or, (16/1)+(9/4)The common denominator of the two fractions is 4Adding (64/4)+(9/4) gives 73/4So adding khổng lồ both sides we finally get:x2-3x+(9/4) = 73/4Adding 9/4 has completed the left hand side into a perfect square :x2-3x+(9/4)=(x-(3/2))•(x-(3/2))=(x-(3/2))2 Things which are equal to the same thing are also equal lớn one another. Sincex2-3x+(9/4) = 73/4 andx2-3x+(9/4) = (x-(3/2))2 then, according lớn the law of transitivity,(x-(3/2))2 = 73/4We"ll refer khổng lồ this Equation as Eq. #6.4.1 The Square Root Principle says that When two things are equal, their square roots are equal.Note that the square root of(x-(3/2))2 is(x-(3/2))2/2=(x-(3/2))1=x-(3/2)Now, applying the Square Root Principle lớn Eq.#6.4.1 we get:x-(3/2)= √ 73/4 showroom 3/2 to both sides lớn obtain:x = 3/2 + √ 73/4 Since a square root has two values, one positive and the other negativex2 - 3x - 16 = 0has two solutions:x = 3/2 + √ 73/4 orx = 3/2 - √ 73/4 note that √ 73/4 can be written as√73 / √4which is √73 / 2

Solve Quadratic Equation using the Quadratic Formula

6.5Solvingx2-3x-16 = 0 by the Quadratic Formula.According to lớn the Quadratic Formula,x, the solution forAx2+Bx+C= 0 , where A, B & C are numbers, often called coefficients, is given by :-B± √B2-4ACx = ————————2A In our case,A= 1B= -3C=-16 Accordingly,B2-4AC=9 - (-64) = 73Applying the quadratic formula : 3 ± √ 73 x=—————2 √ 73 , rounded lớn 4 decimal digits, is 8.5440So now we are looking at:x=(3± 8.544 )/2Two real solutions:x =(3+√73)/2= 5.772 or:x =(3-√73)/2=-2.772

Solving a Single Variable Equation:6.6Solve:x-3 = 0Add 3 lớn both sides of the equation:x = 3